2001
DOI: 10.1152/ajpheart.2001.281.3.h1163
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II and VEGF are involved in angiogenesis induced by short-term exercise training

Abstract: Results from our laboratory have suggested a pathway involving angiotensin II type 1 (AT(1)) receptors and vascular endothelial growth factor (VEGF) in angiogenesis induced by electrical stimulation. The present study investigated if similar mechanisms underlie the angiogenesis induced by short-term exercise training. Seven days before training and throughout the training period, male Sprague-Dawley rats received either captopril or losartan in their drinking water. Rats underwent a 3-day treadmill training pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
160
3
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(171 citation statements)
references
References 39 publications
4
160
3
4
Order By: Relevance
“…Previous studies from our laboratory (2,3) demonstrated that the physiological inhibition of RAS with a high-salt diet or pharmacological inhibition with an angiotensin-converting enzyme inhibitor and ANG II type 1 receptor blocker significantly attenuates angiogenesis in skeletal muscle after electrical stimulation or exercise. The mechanisms responsible for these responses still need to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our laboratory (2,3) demonstrated that the physiological inhibition of RAS with a high-salt diet or pharmacological inhibition with an angiotensin-converting enzyme inhibitor and ANG II type 1 receptor blocker significantly attenuates angiogenesis in skeletal muscle after electrical stimulation or exercise. The mechanisms responsible for these responses still need to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…First, increases in IGF-1 and VEGF occur peripherally in response to activity to stimulate tissue and vascular system growth and repair, which improves oxygen delivery to muscles and increases aerobic performance [49,50]. For example, VEGF signalling regulates muscle capillary density, which is a major determinant of maximal aerobic capacity across mammals [51,52]. Second, BDNF and IGF-1 facilitate lipid oxidation in muscles [53] and glucose metabolism [1], which are essential for energy regulation during submaximal activity [54].…”
Section: (A) Neurotrophins and Growth Factorsmentioning
confidence: 99%
“…The relationship between VO 2,max and brain size across mammals is likely to be related to differences in VEGF expression in more athletic taxa [6], because VO 2,max is positively correlated with the volume of muscle capillary networks across mammals, driven by the need to deliver oxygen during APA [52]. Because skeletal muscle capillarity is regulated by VEGF [51,69], the increased volume of the capillary network found in mammals with high aerobic capacities may be due to evolutionarily altered VEGF signalling.…”
Section: Evolutionary Links Between Aerobic Physical Activity and Neumentioning
confidence: 99%
“…This was likely to be due to the different time course of gene activation versus protein expression. The mRNAs for these molecules tend to increase early in the training and are transient [27] ; by the time we assayed the tissues (after four weeks' training), the mRNA levels had declined to protect against the negative effects of ACE overexpression [28][29][30][31] . Thus, these data indicated that the LHTL training protocol markedly decreased ACE gene expression which some studies have suggested that down-regulation of ACE gene expression was beneficial for long-term exercise training [15] .…”
Section: Wwwchinapharcom Shi W Et Almentioning
confidence: 92%
“…(E and F) shows that the endocardium is thinner in the LLS heart compared to the LHTL heart. [27] . In addition, the over-expression of ACE can cause adaptive hypertrophy of the cardiac muscle, resulting in reduced cardiac contractility and various pathologies that can be reversed through the administration of ACE inhibitors [32] .…”
Section: Wwwchinapharcom Shi W Et Almentioning
confidence: 99%